Effect of Proposed Large Dams on Water Flows and Hydropower Production in the Sekong, Sesan and Srepok Rivers of the Mekong Basin. (16th June 2016) - Piman, T.; Cochrane, T. A.; Arias, M. E.
Abstract: Water flow patterns in the Mekong are changing because of on‐going rapid hydropower development triggered by economic growth. Of immediate concern are the current and proposed hydropower dams in the transboundary Srepok, Sesan and Srekong (3S) Rivers, which contribute up to 20% of the Mekong's annual flows, have a large potential for energy production and provide critical ecosystem services to the downstream Tonle Sap Lake and Mekong Delta. The objective of this paper is to determine how the operation of the proposed largest individual dams and cascade dam schemes in the 3S Rivers will affect flow regimes and energy production. Daily flows were simulated over 20 years using the Soil and Water Assessment Tool and HEC‐ResSim models for a range of dam development and operations scenarios. The development of all dams in the 3S basin under an operation scheme to maximize individual electricity production results in an average 98% increase in dry season flows at the 3S outlet. Over 55% of dry season flows changes are caused by seven proposed large dams, with the Lower Srepok 3 project causing the highest impact. The seven large dams will generate 33.0 GWh/day with a water volume of 17 679 x 10 6  m 3, compared with the current and definite future dams generating 73.2 GWh/day with a much lower volume of 6616 x 10 6  m 3 . When a cascade of dams are operational, downstream dams with small reservoirs will produce more energy. However, the marginal increase in energy production from the development of additional dams in the 3S basin will decline rapidly relative to the required water storage increase, . Strategic decision‐making on the future of each large proposed dam in the 3S basin needs to be considered by local governments after understanding cumulative operation effects and with further consideration to the potential impact on downstream ecosystem productivity and livelihoods. Copyright © 2016 John Wiley & Sons, Ltd.